Nurse-patient dyads linking nurse & patient characteristics to patient satisfaction - Tejero, Lourdes Marie S. (Manila College of Nursing UP Manila, 2009)
Nursing is actualized in an encounter. The nurse's goal of patient's well-being is realized mainly through the interaction between nurse and patient. Such an interaction is not just then an irrelevant occurrence, but a human experience, creating relational links between the nurse and patient. As such, the nurse and patient are no longer separate entities during the interaction, but a dyad. The nurse-patient dyad becomes not just the sum total of the characteristics of the two persons, but an integration of their characteristics working synergistically, thereby bringing about optimum outcomes of care.
Thesis (PhD) -- University of the Philippines Manila.
Keywords: Nurse-Patient relations; Patient satisfaction